Method for manufacturing nonaqueous electrolyte secondary battery
By adding thiophosphate to the positive electrode active material layer of the nonaqueous electrolyte secondary battery and performing initial charging and aging treatment to form a film, the problem of increasing resistance of the nonaqueous electrolyte secondary battery at high temperature is solved, and significantly improved Battery durability and performance stability.
Patent Information
- Application Number
- CN202410895907.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-11
- Filing Date
- 2024-07-05
- Publication Date
- 2025-01-07
AI Technical Summary
The existing nonaqueous electrolyte secondary batteries have increased resistance when placed at high temperatures, and it is difficult for the prior art to effectively suppress this phenomenon.
By adding 1% to 10% of the thiophosphate to the positive electrode active material layer, and performing initial charging and aging treatment until the voltage above the starting potential of the decomposition of the thiophosphate is formed to suppress the increase in resistance.
It effectively suppresses the increase in resistance of the nonaqueous electrolyte secondary battery when placed at long-term high temperatures, and improves the durability and performance stability of the battery.
Smart Images

Figure CN119275362A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a nonaqueous electrolyte secondary battery. Background Art
[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries have been used favorably as portable power sources for personal computers and portable terminals, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs).
[0003] The positive electrode of the non-aqueous electrolyte secondary battery typically includes a positive electrode active material layer containing a positive electrode active material. In order to improve the performance of the non-aqueous electrolyte secondary battery, it is known to make the positive electrode active material layer contain an additive (so-called positive electrode additive) that forms a film on the surface of the positive electrode active material. For example, in patent document 1, it is recorded that by making the positive electrode active material layer contain thiophosphate or thiophosphate salt, the cycle characteristics of the non-aqueous electrolyte secondary battery are improved. For example, in patent document 2, it is recorded that by making the positive electrode active material layer contain lithium phosphate, the output characteristics and cycle characteristics of the non-aqueous electrolyte secondary battery are improved when a high-potential positive electrode active material is used.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-352804
[0007] Patent Document 2: Japanese Patent Application Publication No. 2016-062644 Summary of the invention
[0008] However, as a result of intensive research by the present inventors, it has been found that in the above-mentioned prior art, there is room for improvement in the high-temperature storage characteristics of non-aqueous electrolyte secondary batteries, specifically, there is room for improvement in suppressing the increase in resistance when non-aqueous electrolyte secondary batteries are placed at high temperatures for a long time.
[0009] Therefore, an object of the present invention is to provide a method for producing a nonaqueous electrolyte secondary battery capable of suppressing an increase in resistance when left at high temperature for a long period of time.
[0010] The method for manufacturing a non-aqueous electrolyte secondary battery disclosed herein includes: a process of preparing a battery assembly including a positive electrode, a negative electrode and a non-aqueous electrolyte; a process of performing an initial charge on the battery assembly; and a process of performing an aging treatment on the battery assembly that has been subjected to the initial charge. The positive electrode includes a positive electrode collector and a positive electrode active material layer supported by the positive electrode collector. The positive electrode active material layer contains a positive electrode active material and a thiophosphate. The content ratio of the thiophosphate in the positive electrode active material layer is 1% by mass to 10% by mass. The initial charge is performed until the voltage reaches a voltage above the decomposition start potential of the thiophosphate. The aging treatment is performed while the battery assembly is charged to a voltage above the decomposition start potential of the thiophosphate.
[0011] According to such a configuration, it is possible to provide a method for producing a nonaqueous electrolyte secondary battery capable of suppressing an increase in resistance when the battery is left at high temperature for a long period of time. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a flowchart showing each step of a method for manufacturing a nonaqueous electrolyte secondary battery according to one embodiment of the present invention.
[0013] Figure 2 This is a schematic diagram for explaining the structure of a wound electrode body of a non-aqueous electrolyte secondary battery manufactured according to one embodiment of the present invention.
[0014] Figure 3 This is a cross-sectional view schematically showing the structure of a non-aqueous electrolyte secondary battery manufactured according to one embodiment of the present invention. DETAILED DESCRIPTION
[0015] The following describes the embodiments of the present invention with reference to the accompanying drawings. Furthermore, matters not mentioned in this specification, that is, matters required for the implementation of the present invention, can be understood as design matters for those skilled in the art based on the prior art in this field. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, the same figure marks are marked on the components and parts that play the same role for illustration. In addition, the dimensional relationships (length, width, thickness, etc.) in each figure do not reflect the actual dimensional relationships. It should be noted that A and B are included in the numerical range expressed as "A~B" in this specification.
[0016] It should be noted that in this specification, "secondary battery" refers to a storage device that can be repeatedly charged and discharged. In addition, in this specification, "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as charge carriers and realizes charge and discharge by the movement of charges accompanied by lithium ions between positive and negative electrodes.
[0017] The present invention will be specifically described below with reference to an embodiment in which the nonaqueous electrolyte secondary battery is a flat square lithium ion secondary battery as an example, but the present invention is not intended to be limited to the technical solutions described in this embodiment.
[0018] exist Figure 1 The steps of the method for manufacturing the non-aqueous electrolyte secondary battery according to the present embodiment are shown in FIG. Figure 2 Schematically showing the structure of an electrode body of a lithium ion secondary battery as an example of a non-aqueous electrolyte secondary battery obtained by the manufacturing method according to the present embodiment. Figure 3 Schematically shows the internal structure of a lithium ion secondary battery as an example of a non-aqueous electrolyte secondary battery obtained by the production method according to the present embodiment.
[0019] The method for manufacturing the non-aqueous electrolyte secondary battery according to the present embodiment is as follows Figure 1 As shown, it includes: a step of preparing a battery assembly including a positive electrode, a negative electrode and a non-aqueous electrolyte (hereinafter also referred to as an "assembly preparation step") S101, a step of performing an initial charge on the battery assembly (hereinafter also referred to as an "initial charging step") S102, and a step of performing an aging treatment on the battery assembly that has been initially charged (hereinafter also referred to as an "aging step") S103. The positive electrode includes a positive electrode collector and a positive electrode active material layer supported by the positive electrode collector. The positive electrode active material layer contains a positive electrode active material and a thiophosphate. The content ratio of the thiophosphate in the positive electrode active material layer is 1% by mass to 10% by mass. The initial charge is performed until the voltage reaches a voltage above the decomposition start potential of the thiophosphate. The aging treatment is performed while the battery assembly is charged to a voltage above the decomposition start potential of the thiophosphate. The following describes each step of the method for manufacturing a non-aqueous electrolyte secondary battery according to the present embodiment.
[0020] First, the assembly preparation step S101 will be described. In the assembly preparation step S101, a battery assembly including the positive electrode 50, the negative electrode 60, and the non-aqueous electrolyte 80 is prepared.
[0021] The positive electrode 50 used in the assembly preparation step S101 is typically, for example, Figure 2 As shown, it includes a positive electrode current collector 52 and a positive electrode active material layer 54 supported by the positive electrode current collector 52. The positive electrode active material layer 54 can be provided on one side of the positive electrode current collector 52, or on both sides, preferably on both sides. Figure 2 As shown, typically, a positive electrode 50 is provided with a positive electrode active material layer non-formed portion 52 a (ie, a portion where the positive electrode active material layer 54 is not formed and the positive electrode collector 52 is exposed).
[0022] As the positive electrode current collector 52, a known positive electrode current collector used for lithium ion secondary batteries can be used, and examples thereof include sheets or foils made of metals with good conductivity (such as aluminum, nickel, titanium, stainless steel, etc.). As the positive electrode current collector 52, aluminum foil is preferred.
[0023] The size of the positive electrode current collector 52 is not particularly limited and can be appropriately determined according to the battery design. When aluminum foil is used as the positive electrode current collector 52, its thickness is not particularly limited, and is, for example, 5 μm to 35 μm, preferably 7 μm to 20 μm.
[0024] The positive electrode active material layer 54 contains a positive electrode active material and a thiophosphate. As the positive electrode active material, a known positive electrode active material for a lithium ion secondary battery can be used. Specifically, for example, as the positive electrode active material, a lithium composite oxide, a lithium transition metal phosphate compound, etc. can be used. There is no particular limitation on the crystal structure of the positive electrode active material, and it can be a layered structure, a spinel structure, an olivine structure, etc.
[0025] As the lithium composite oxide, preferably a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element. Specific examples thereof include lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium iron nickel manganese composite oxides.
[0026] It should be noted that in this specification, the so-called "lithium nickel cobalt manganese composite oxide" is a term for an oxide containing one or more additional elements other than Li, Ni, Co, Mn, and O in addition to oxides having Li, Ni, Co, Mn, and O as constituent elements. Examples of the additional elements include transition metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn, typical metal elements, and the like. In addition, the additional elements may be semi-metallic elements such as B, C, Si, and P, and non-metallic elements such as S, F, Cl, Br, and I. This is also true for the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.
[0027] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO 4 ), lithium manganese phosphate (LiMnPO 4 ), and lithium manganese iron phosphate.
[0028] These positive electrode active materials may be used alone or in combination of two or more.
[0029] The thiophosphate is decomposed by the initial charging of the subsequent initial charging step S102, and a film from the thiophosphate is formed on the surface of the positive electrode active material. The initial charging is performed at a voltage above the decomposition start potential of the thiophosphate. However, only during the initial charging, a voltage above the decomposition start potential of the thiophosphate can be applied to the lithium ion secondary battery, so the upper limit potential of the positive electrode active material in the general use mode of the lithium ion secondary battery can be lower than the decomposition start potential of the thiophosphate.
[0030] From the perspective of battery characteristics and the stability of the crystal structure during initial charging, as the positive electrode active material, a lithium composite oxide having a layered structure is preferred. The lithium composite oxide preferably contains Ni. Therefore, as the positive electrode active material, lithium nickel cobalt manganese composite oxides and lithium nickel cobalt aluminum composite oxides are preferred, and lithium nickel cobalt manganese composite oxides are more preferred.
[0031] The ratio of Ni to the total amount of metal elements other than Li in the lithium composite oxide is preferably 20 mol % to 60 mol %, more preferably 30 mol % to 50 mol %.
[0032] The average particle size (median diameter: D50) of the positive electrode active material is not particularly limited, and is, for example, 0.05 μm or more and 25 μm or less, preferably 1 μm or more and 20 μm or less, and more preferably 3 μm or more and 15 μm or less. Furthermore, the average particle size (D50) of the positive electrode active material can be obtained, for example, by a laser diffraction scattering method.
[0033] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, and is, for example, 80 mass % or more, preferably 85 mass % or more, and more preferably 87 mass % or more.
[0034] The thiophosphate is a component (so-called positive electrode additive) added to the positive electrode in order to form a film on the surface of the positive electrode active material by the initial charge of the subsequent initial charge step S102. The thiophosphate is a salt of a thiophosphate anion and a cation represented by the following formula (1). The thiophosphate is typically an inorganic salt and therefore typically does not contain an organic group. The thiophosphate anion is a trivalent anion, and the cation is a monovalent, divalent, or trivalent cation (particularly a metal cation).
[0035] [Chemistry 1]
[0036]
[0037] Since the thiophosphate anion greatly contributes to the film formation, the type of cation is not particularly limited. Examples of cations include Li +、Na + , K + Alkali metal cations such as Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ Alkaline earth metal cations such as Zn 2+ Group 12 cations such as Al 3+ The cations of the Group 13 elements are preferably cations of alkali metals. Therefore, the thiophosphate is preferably an alkali metal salt of thiophosphate.
[0038] As the thiophosphate salt, sodium thiophosphate is particularly preferred from the viewpoint of easy availability, and as the thiophosphate salt, lithium thiophosphate is particularly preferred from the viewpoint of battery performance.
[0039] The greater the proportion of thiophosphate contained in the positive electrode active material layer 54, the higher the resistance increase suppression effect when the lithium ion secondary battery 100 is placed at high temperature for a long time. Therefore, the proportion of thiophosphate contained in the positive electrode active material layer 54 (that is, the mass proportion of thiophosphate relative to the total mass of all components of the positive electrode active material layer 54) is 1% by mass or more, preferably 2% by mass or more, more preferably 2.5% by mass or more, and more preferably 3% by mass or more. On the other hand, if the proportion of thiophosphate contained is large, the initial resistance tends to increase. Therefore, the proportion of thiophosphate contained in the positive electrode active material layer 54 is less than 10% by mass, preferably less than 8% by mass, more preferably less than 7.5% by mass, and more preferably less than 7% by mass.
[0040] The positive electrode active material layer 54 may contain only thiophosphate as a positive electrode additive, and may further contain other positive electrode additives within a range that does not significantly inhibit the effects of the present invention.
[0041] The positive electrode active material layer 54 may contain components other than the above-mentioned positive electrode active material and thiophosphate (i.e., optional components). As examples of the optional components, conductive materials, adhesives, etc. can be listed. As conductive materials, for example, carbon black (e.g., acetylene black), carbon nanotubes (CNTs), graphite and other carbon materials can be preferably used. As adhesives, for example, polyvinylidene fluoride (PVDF) and the like can be used. In the case of using CNT as a conductive material, the positive electrode active material layer 54 may further contain a dispersant for CNT.
[0042] The content of the conductive material in the positive electrode active material layer 54 is not particularly limited, but is preferably 0.1% by mass or more and 15% by mass or less, and more preferably 0.5% by mass or more and 13% by mass or less. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably 1% by mass or more and 15% by mass or less, and more preferably 1.5% by mass or more and 10% by mass or less.
[0043] The thickness of the positive electrode active material layer 54 is not particularly limited, and is, for example, 10 μm or more and 300 μm or less, and preferably 20 μm or more and 200 μm or less.
[0044] The positive electrode sheet 50 may include an insulating layer (not shown) at the boundary between the positive electrode active material layer non-formed portion 52a and the positive electrode active material layer 54. The insulating layer includes, for example, ceramic particles.
[0045] The positive electrode 50 can be produced and prepared by a known method. For example, a positive electrode paste containing a positive electrode active material, a thiophosphate, and an optional component is prepared, and the positive electrode paste is applied to the positive electrode collector 52, dried, and pressed as needed to prepare the positive electrode 50. In addition, the term "paste" in this specification is used as a term that also includes forms called "slurry" and "ink".
[0046] The negative electrode 60 used in the assembly preparation step S101 may be a known negative electrode used for lithium ion secondary batteries. The negative electrode 60 is typically, for example, Figure 2 As shown, it includes a negative electrode current collector 62 and a negative electrode active material layer 64 supported by the negative electrode current collector 62. The negative electrode active material layer 64 can be provided on one side of the negative electrode current collector 62, or on both sides, preferably on both sides. Typically, as Figure 2 As shown, the negative electrode 60 is provided with a negative electrode active material layer non-formed portion 62 a (ie, a portion where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed).
[0047] A known negative electrode current collector used for lithium ion secondary batteries can be used as the negative electrode current collector 62 , and examples thereof include sheets or foils made of metals with good conductivity (eg, copper, nickel, titanium, stainless steel, etc.). The negative electrode current collector 62 is preferably copper foil.
[0048] The size of the negative electrode current collector 62 is not particularly limited and can be appropriately determined according to the battery design. When copper foil is used as the negative electrode current collector 62, its thickness is not particularly limited, and is, for example, 5 μm to 35 μm, preferably 7 μm to 20 μm.
[0049] The negative electrode active material layer 64 contains a negative electrode active material. As the negative electrode active material, for example, carbon materials such as graphite, hard carbon, and soft carbon can be used. The graphite may be natural graphite or artificial graphite, and the graphite may be amorphous carbon-coated graphite in the form of being coated with an amorphous carbon material.
[0050] The average particle size (median diameter: D50) of the negative electrode active material is not particularly limited, and is, for example, 0.1 μm or more and 50 μm or less, preferably 1 μm or more and 25 μm or less, and more preferably 5 μm or more and 20 μm or less. The average particle size (D50) of the negative electrode active material can be obtained, for example, by laser diffraction scattering.
[0051] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), etc. can be used. As the thickener, for example, carboxymethyl cellulose (CMC) can be used.
[0052] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or more, more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, more preferably 0.5% by mass or more and 2% by mass or less.
[0053] The thickness of the negative electrode active material layer 64 is not particularly limited, and is, for example, 10 μm or more and 300 μm or less, and preferably 20 μm or more and 200 μm or less.
[0054] The negative electrode 60 can be produced and prepared by a known method. For example, the negative electrode 60 can be prepared by preparing a negative electrode paste containing a negative electrode active material and optional components, applying the negative electrode paste to the negative electrode collector 62, drying it, and performing a pressing process as needed.
[0055] Positive Electrode 50 and Negative Electrode 60 Typically, the positive electrode 50 and the negative electrode 60 are used as an electrode body 20 stacked via a separator 70. The electrode body 20 may be a stacked electrode body or a wound electrode body. In the example shown in the figure, the electrode body 20 is a wound electrode body.
[0056] As the separator 70, for example, a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, polyamide, etc. can be cited. The porous sheet can be a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). A heat-resistant layer (HRL) can be provided on the surface of the separator 70.
[0057] The thickness of the separator 70 is not particularly limited, and is, for example, 5 μm to 50 μm, preferably 10 μm to 30 μm. The air permeability of the separator 70 measured by the Gray test is not particularly limited, and is preferably 350 sec / 100 cc or less.
[0058] The electrode body 20 can be produced by a known method. As shown in the example in the figure, when the electrode body 20 is a wound electrode body, it can be prepared as follows, for example.
[0059] First, the positive electrode sheet 50 and the negative electrode sheet 60 are overlapped so that the separator sheet 70 is interposed therebetween. Then, the separator sheet 70 is stacked. Figure 2 As shown, the positive electrode active material layer non-formed portion 52 a of the positive electrode sheet 50 and the negative electrode active material layer non-formed portion 62 a of the negative electrode sheet 60 overlap so as to protrude from the widthwise ends of the two separator sheets 70 in opposite directions.
[0060] The obtained laminate is wound up. The winding of the laminate can be carried out according to a known method. For example, it can be carried out by using a winding machine including a known winding core and winding the laminate up on the outer peripheral surface of the winding core. The winding conditions can be the same as the known conditions.
[0061] Next, the wound stack is subjected to a pressing process to produce a flat wound electrode body. The pressing process can be performed by pressing the wound stack in the above-mentioned winding step using a known pressing device used in the manufacture of a general flat wound electrode body. The pressing conditions can be the same as the known conditions.
[0062] On the other hand, the battery case 30 is prepared. Specifically, Figure 3 As shown, a main body of a battery case 30 having an opening and a cover of the battery case 30 are prepared. The opening has a size that allows the wound electrode body 20 to be inserted. The cover has a size that blocks the opening of the main body of the battery case 30. In addition, a thin-walled safety valve 36 and an injection port (not shown) for injecting a non-aqueous electrolyte are provided on the cover, and the safety valve 36 is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or above. For the battery case 30, for example, a metal material such as aluminum that is lightweight and has good thermal conductivity is used.
[0063] In addition, prepare nonaqueous electrolyte 80. Nonaqueous electrolyte 80 typically contains nonaqueous solvent and supporting salt (electrolyte salt). As nonaqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, lactones used in the electrolyte of general lithium ion secondary batteries can be used without particular limitation. Among them, carbonates and esters are preferred, and as its specific example, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC), methyl acetate, methyl propionate, etc. can be illustrated. Such nonaqueous solvent can be used alone, or two or more are appropriately used in combination.
[0064] As the supporting salt, for example, lithium salts such as LiPF6, LiBF4, and lithium bis(fluorosulfonyl)imide (LiFSI) (preferably LiPF6) can be preferably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.
[0065] The non-aqueous electrolyte 80 may contain components other than the above-mentioned components (eg, various additives) as long as the effects of the present invention are not significantly impaired.
[0066] For example, when the non-aqueous electrolyte 80 contains an oxalic acid complex as a film forming agent, the resistance increase when placed at high temperature for a long time can be further suppressed. Examples of the oxalic acid complex include difluoro (oxalate) lithium borate (LiBF2 (C2O4)), bis (oxalate) lithium borate (LiB (C2O4)2), tetrafluoro (oxalate) lithium phosphate (LiPF4 (C2O4)), difluoro bis (oxalate) lithium phosphate (LiPF2 (C2O4)2), etc. Among them, lithium bis (oxalate) borate (LiBOB) is preferred because of its high film forming ability.
[0067] The concentration of the oxalic acid complex in the non-aqueous electrolyte 80 is, for example, 0.1 mass % to 1.5 mass %, preferably 0.3 mass % to 1.5 mass %, more preferably 0.5 mass % to 1.5 mass %. From the viewpoint of balancing the initial resistance and the high-temperature storage characteristics, the concentration of the oxalic acid complex in the non-aqueous electrolyte 80 is particularly preferably 0.5 mass % to 1.0 mass %.
[0068] Examples of other additives include film-forming agents such as vinylene carbonate (VC); gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB); and thickeners.
[0069] Next, the positive terminal 42 and the positive collector plate 42a and the negative terminal 44 and the negative collector plate 44a are installed on the cover of the battery case 30. The positive active material layer non-forming portion 52a and the negative active material layer non-forming portion 62a of the positive collector plate 42a and the negative collector plate 44a exposed at the end of the wound electrode body 20 are welded by ultrasonic welding, resistance welding, etc. Then, the wound electrode body 20 is accommodated in the inside of the main body of the battery case 30 from the opening of the main body thereof, and the main body of the battery case 30 and the cover are welded by laser welding or the like.
[0070] Next, a nonaqueous electrolyte 80 is injected from the injection port of the cover of the battery case 30. The injection of the nonaqueous electrolyte 80 can be performed according to a known method. After the nonaqueous electrolyte 80 is injected, the injection port is sealed to obtain the battery assembly 100. The sealing of the injection port can be performed according to a known method.
[0071] Next, the initial charging step S102 is described. In the initial charging step S102, the battery assembly 100 is initially charged. The initial charging is performed until the voltage reaches a voltage higher than the decomposition start potential of the thiophosphate. As a result, the thiophosphate in the positive electrode active material layer 54 is decomposed, and a film derived from the thiophosphate can be formed on the surface of the positive electrode active material.
[0072] Among them, thiophosphates as positive electrode additives have a relatively low decomposition starting potential. For example, the decomposition starting potential of Li3PO3 is 4.50V (vsLi + / Li) (i.e., 4.50 V based on metallic lithium), while the decomposition starting potential of sodium thiophosphate (Na3PSO3) is 4.35 V (vsLi + / Li). Therefore, when the battery assembly 100 is initially charged, the thiophosphate can be efficiently decomposed, and a high-quality film can be formed on the surface of the positive electrode active material layer. As a result, the resistance increase of the lithium ion secondary battery 100 when it is placed at high temperature for a long time can be suppressed.
[0073] The upper limit voltage of the initial charge depends on the type of thiophosphate. However, if the upper limit voltage of the initial charge is too high, it may cause excessive decomposition of the non-aqueous electrolyte 80, structural degradation of the positive electrode active material, etc. Therefore, the upper limit voltage of the initial charge is preferably set when the positive electrode potential becomes 4.70V (vsLi + / Li), more preferably, the positive electrode potential becomes 4.50V (vsLi + / Li) voltage.
[0074] It is preferred to perform initial charging until the potential of the positive electrode 50 reaches 4.35 V (vsLi + / Li)~4.70V(vsLi + / Li), more preferably until it becomes 4.35V (vsLi + / Li)~4.50V(vsLi + / Li) voltage.
[0075] The initial charge can be performed according to a known method. Specifically, it can be performed by applying a predetermined voltage between the positive electrode 50 and the negative electrode 60 using a known voltage application device (not shown). There is no particular limitation on the current value, but it is preferably less than 1C, more preferably greater than 0.1C and less than 0.5C. Furthermore, after charging, discharging is usually performed. In the initial charge, charging may be performed only once or multiple times (for example, 2 to 3 times).
[0076] Next, the aging process S103 is described. In the aging process S103, the battery assembly 100 that has been initially charged in the previous process is subjected to an aging treatment. The aging treatment is performed in a state where the battery assembly 100 is charged to a voltage that is higher than the decomposition start potential of the thiophosphate. As a result, the thiophosphate in the positive electrode active material layer 54 is further decomposed, and a film derived from the thiophosphate can be further formed on the surface of the positive electrode active material, thereby further improving the quality of the film.
[0077] If the voltage of the battery assembly 100 in the aging step S103 is too high, excessive decomposition of the non-aqueous electrolyte 80 and structural degradation of the positive electrode active material may occur. Therefore, the voltage of the battery assembly 100 is preferably such that the positive electrode potential becomes 4.70 V (vsLi + / Li) or less, and more preferably, the positive electrode potential becomes 4.50V (vsLi + / Li) voltage is below.
[0078] Therefore, the aging treatment is preferably performed when the potential of the positive electrode 50 is charged to 4.35 V (vsLi + / Li)~4.70V(vsLi + / Li), more preferably 4.35V (vsLi + / Li)~4.50V(vsLi + / Li) is performed under a voltage state.
[0079] The temperature of the aging treatment is not particularly limited, but is preferably a temperature higher than room temperature. Specifically, the temperature of the aging treatment is preferably 40°C to 100°C, and more preferably 40°C to 75°C. The time of the aging treatment is not particularly limited. The time of the aging treatment is preferably 1 hour to 72 hours, and more preferably 4 hours to 24 hours.
[0080] Therefore, the aging treatment is particularly preferably performed at a temperature within a range of 40° C. to 75° C. for 4 to 24 hours.
[0081] The aging step S103 can be performed by a known method. Specifically, for example, the aging step S103 can be performed by adjusting the charge state of the battery assembly 100 using a known voltage application device (not shown) and leaving the battery assembly 100 to stand in a thermostatic chamber or the like.
[0082] In the aging step S103, the thiophosphate is also decomposed, and a film from the thiophosphate is formed on the surface of the positive electrode active material. Therefore, by performing the initial charging step S102 and the aging step S103, the thiophosphate can be efficiently decomposed and a film can be effectively formed on the surface of the positive electrode active material.
[0083] By going through the above steps, a lithium ion secondary battery 100 can be obtained. In the lithium ion secondary battery 100, a high-quality film derived from thiophosphate is formed on the surface of the positive electrode active material, and the film can suppress the decomposition of the non-aqueous electrolyte 80 during storage. As a result, in the lithium ion secondary battery 100, the increase in resistance when placed at high temperature for a long time is suppressed. Therefore, according to the manufacturing method involved in this embodiment, a lithium ion secondary battery 100 with excellent durability can be manufactured.
[0084] The lithium-ion secondary battery 100 can be used in various applications. Specific applications include portable power supplies for personal computers, portable electronic devices, portable terminals, etc.; vehicle driving power supplies such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); batteries for small power storage devices, etc., among which vehicle driving power supplies are preferred. The lithium-ion secondary battery 100 can also be typically used in the form of a battery pack in which a plurality of batteries are connected in series and / or in parallel.
[0085] Furthermore, as an example, a square lithium-ion secondary battery 100 including a flat wound electrode body 20 is described. However, by using the method for manufacturing a non-aqueous electrolyte secondary battery disclosed herein, a lithium-ion secondary battery including a stacked electrode body (i.e., an electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked) can also be manufactured. In addition, by using the method for manufacturing a non-aqueous electrolyte secondary battery disclosed herein, coin-type lithium-ion secondary batteries, button-type lithium-ion secondary batteries, cylindrical lithium-ion secondary batteries, and laminated shell-type lithium-ion secondary batteries can also be manufactured. In addition, by using the method for manufacturing a non-aqueous electrolyte secondary battery disclosed herein, non-aqueous electrolyte secondary batteries other than lithium-ion secondary batteries can also be manufactured.
[0086] The following describes an embodiment related to the present invention, but it is not intended to limit the present invention to the technical solutions shown in this embodiment.
[0087] Examples 1 to 6 and Comparative Examples 1 to 6
[0088] [Manufacturing of lithium-ion secondary battery assembly]
[0089] LiNi as the positive electrode active material powder 0.5 Co 0.2 Mn 0.3 O2 (NCM), acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder are mixed in a mass ratio of NCM:AB:PVdF=90:5:5. The positive electrode additives shown in Table 1 are added thereto so that the content ratio in the positive electrode active material layer becomes the amount shown in Table 1, and mixed with N-methylpyrrolidone (NMP). Thus, a slurry for forming a positive electrode active material layer is prepared. The slurry is applied to both sides of the aluminum foil and then dried to form a positive electrode active material layer. At this time, the total unit area mass of the two sides is 15 mg / cm 2 Next, the positive electrode active material layer was pressed to a density of 2.5 g / cm 3 , thereby obtaining a positive electrode sheet.
[0090] Natural graphite (C) as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed with ion exchange water at a mass ratio of C: SBR: CMC = 97: 2: 1 to prepare a slurry for forming a negative electrode active material layer. The slurry was applied to both sides of the copper foil and dried to form a negative electrode active material layer. The total unit area mass of the two sides was 9 mg / cm 2 Next, the negative electrode active material layer was pressed to a density of 1.2 g / cm 3 , thereby obtaining a negative electrode sheet.
[0091] In addition, a polyolefin porous film was prepared as a separator. The prepared positive electrode sheet and negative electrode sheet were stacked via the separator to prepare a stacked electrode body. Terminals were attached to the electrode body and the electrode body was housed in an aluminum battery case.
[0092] A mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 25:40:35 is prepared. In Examples 1, 2 and Comparative Examples 1 to 6, a non-aqueous electrolyte is prepared by dissolving LiPF6 at a concentration of 1.1 mol / L in the mixed solvent. In Examples 3 to 6, a non-aqueous electrolyte is prepared by dissolving LiPF6 at a concentration of 1.1 mol / L in the mixed solvent, and further, dissolving lithium bis(oxalate)borate (LiBOB) in an amount as shown in Table 1. After the prepared non-aqueous electrolyte is injected into the battery case, the battery case is sealed to obtain a battery assembly.
[0093] [Initial charging]
[0094] The obtained battery assembly was placed in a thermostatic chamber at 25°C. The battery assembly was charged to a predetermined upper limit voltage using a current value of 0.1C and then discharged to 3.0V using a constant current. The predetermined upper limit voltage was set to the positive electrode potential (vsLi) shown in Table 1. + This charge and discharge was performed twice as the initial charge.
[0095] [Aging treatment]
[0096] The battery assembly after initial charge was adjusted to a positive electrode potential (vsLi) as shown in Table 1. + / Li). Then, the battery assembly was placed in a thermostatic chamber at 60°C and aged for 12 hours. As described above, a lithium ion secondary battery was obtained.
[0097] [Initial characteristics evaluation]
[0098] The lithium ion secondary batteries prepared in each example and each comparative example were charged at a constant current value of 0.1 C to the same upper limit voltage as the initial charge, and then discharged at a constant current to 3.0 V. The discharge capacity at this time was measured and set as the initial capacity.
[0099] The initial capacity is set to SOC100%, and the lithium ion secondary battery is adjusted to SOC50% at 25°C. Then, the lithium ion secondary battery is placed in a constant temperature layer at -10°C and discharged for 10 seconds at a current value of 10C. The voltage change ΔV at this time is measured, and the output resistance of the lithium ion secondary battery is calculated as the initial resistance using the voltage change ΔV and the current value. The results are shown in Table 1.
[0100] [Evaluation of high temperature storage characteristics]
[0101] The lithium-ion secondary battery was adjusted to SOC 80% at a temperature of 25°C. The lithium-ion secondary battery was placed in a constant temperature layer at 60°C and stored for 60 days. Then, the output resistance after storage was measured using the same method as the initial resistance. The resistance increase rate (%) was calculated using the formula: (output resistance after high temperature storage / initial resistance) × 100. The results are shown in Table 1.
[0102] [Table 1]
[0103]
[0104] The decomposition starting potential of sodium thiophosphate (Na3PSO3) is 4.35V (vsLi + / Li). Comparative Examples 1 and 2 are examples of reducing the voltage in the aging process, and in the aging process, a coating from thiophosphoric acid cannot be formed. Comparative Example 3 is an example of reducing the voltage in the initial charging process and the aging process, and in the initial charging process and the aging process, a coating from thiophosphoric acid is not formed. From the comparison of Comparative Examples 1 and 2 with Comparative Example 3, it can be seen that by initially charging the battery assembly until the voltage becomes higher than the decomposition start potential of Na3PSO3 and forming a film, the increase in resistance during high-temperature storage can be suppressed. In addition, from the comparison of Examples 1 and 2 and Comparative Examples 1 and 2, it can be seen that by performing an aging treatment while charging the battery assembly to a voltage higher than the decomposition start potential of Na3PSO3, a film is formed, which can further suppress the increase in resistance during high-temperature storage.
[0105] Comparative Example 4 is an example in which no positive electrode additive is used, and Comparative Examples 5 and 6 are examples in which trilithium phosphate and thiophosphate are used as positive electrode additives, respectively. From the comparison between Examples 1 and 2 and Comparative Examples 4 to 6, it can be seen that when the positive electrode additive is thiophosphate, the resistance increase suppression effect during high temperature storage is obtained.
[0106] In addition, Examples 3 to 6 are examples in which LiBOB is contained in the non-aqueous electrolyte solution. From these results, it is understood that when LiBOB is contained in the non-aqueous electrolyte solution, the effect of suppressing the increase in resistance during high-temperature storage is further improved.
[0107] As is apparent from the above, according to the method for producing a nonaqueous electrolyte secondary battery disclosed herein, a nonaqueous electrolyte secondary battery can be produced in which an increase in resistance when left at high temperature for a long period of time is suppressed.
[0108] The specific examples of the present invention have been described in detail above, but these are merely examples and do not limit the claims. The technology described in the claims includes various modifications and changes of the specific examples described above.
[0109] That is, the method for producing a nonaqueous electrolyte secondary battery disclosed herein includes the following items [1] to [7].
[0110] [1] A manufacturing method, which is a manufacturing method for a non-aqueous electrolyte secondary battery, comprising: a step of preparing a battery assembly including a positive electrode, a negative electrode and a non-aqueous electrolyte; a step of performing an initial charge on the battery assembly; and a step of performing an aging treatment on the battery assembly that has been subjected to the initial charge, wherein the positive electrode includes a positive electrode collector and a positive electrode active material layer supported by the positive electrode collector, the positive electrode active material layer contains a positive electrode active material and a thiophosphate, the thiophosphate content in the positive electrode active material layer is 1% by mass to 10% by mass, the initial charge is performed until the voltage reaches a voltage above the decomposition start potential of the thiophosphate, and the aging treatment is performed while the battery assembly is charged to a voltage above the decomposition start potential of the thiophosphate.
[0111] [2] The production method according to item [1], wherein the content ratio of the thiophosphate in the positive electrode active material layer is 3% by mass to 7% by mass.
[0112] [3] The manufacturing method according to item [1] or [2], wherein the initial charging is performed until the potential of the positive electrode reaches 4.35 V (vs Li + / Li)~4.50V(vsLi + / Li), the aging treatment is performed by charging the battery assembly until the potential of the positive electrode reaches 4.35V (vsLi + / Li)~4.50V(vsLi + / Li) is performed under a voltage state.
[0113] [4] The production method according to any one of items [1] to [3], wherein the aging treatment is performed at a temperature in the range of 40° C. to 75° C. for 4 to 24 hours.
[0114] [5] The production method according to any one of items [1] to [4], wherein the thiophosphate is an alkali metal salt of thiophosphate.
[0115] [6] The production method according to any one of items [1] to [5], wherein the positive electrode active material is at least one composite oxide selected from lithium nickel cobalt manganese composite oxides and lithium nickel cobalt aluminum composite oxides.
[0116] [7] The production method according to any one of items [1] to [6], wherein the nonaqueous electrolyte contains lithium bis(oxalato)borate.
Claims
1. A method for manufacturing a non-aqueous electrolyte secondary battery, comprising: A step of preparing a battery assembly including a positive electrode, a negative electrode and a non-aqueous electrolyte; performing an initial charging process on the battery assembly; and a step of subjecting the battery assembly subjected to the initial charge to an aging treatment, The positive electrode includes a positive electrode current collector and a positive electrode active material layer supported by the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and thiophosphate. The content ratio of the thiophosphate in the positive electrode active material layer is 1 mass % to 10 mass %, The initial charge is performed until the voltage reaches a potential higher than the decomposition start potential of the thiophosphate. The aging treatment is performed in a state where the battery assembly is charged to a voltage equal to or higher than a decomposition start potential of the thiophosphate.
2. The manufacturing method according to claim 1, wherein: The content ratio of the thiophosphate in the positive electrode active material layer is 3 mass % to 7 mass %.
3. The manufacturing method according to claim 1, wherein: The initial charge is performed until the potential of the positive electrode reaches 4.35 V (vsLi + / Li)~4.50V(vsLi + / Li), the aging treatment is performed by charging the battery assembly until the potential of the positive electrode reaches 4.35V (vsLi + / Li)~4.50V(vsLi + / Li) is performed under a voltage state.
4. The manufacturing method according to claim 1, wherein: The aging treatment is performed at a temperature within a range of 40° C. to 75° C. for 4 to 24 hours.
5. The manufacturing method according to claim 1, wherein: The thiophosphate is an alkali metal salt of thiophosphoric acid.
6. The manufacturing method according to claim 1, wherein: The positive electrode active material is at least one composite oxide selected from lithium nickel cobalt manganese composite oxides and lithium nickel cobalt aluminum composite oxides.
7. The manufacturing method according to claim 1, wherein: The nonaqueous electrolyte contains lithium bis(oxalate)borate.
Citation Information
Patent Citations
Nonaqueous secondary cell
JP2002352804A
Lithium ion secondary battery and method for manufacturing the same
JP2016062644A